2022
DOI: 10.1039/d2em00005a
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of aqueous transition metals in particulate matter during the dithiothreitol (DTT) oxidative potential assay

Abstract: Transition metals in particulate matter (PM) are hypothesized to have enhanced toxicity based on their oxidative potential (OP). The acellular dithiothreitol (DTT) assay is widely used to measure the OP...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 89 publications
0
1
0
Order By: Relevance
“…Experimentally, they show that less than 10% of the total Mn is in the precipitated form, when the total Mn concentration is less than or equal to 100 mmol L −1 , suggesting a slow kinetics of precipitation. In a recent study, Yalamanchili et al (2022) 81 suggested that under the same conditions the formation of the MnHPO 4 (s) precipitate may not reach equilibrium aer 40 min and could continue to precipitate beyond this time. In our study, this implies that the precipitation of MnHPO 4 (s) can continue in the extracted solution aer ltration.…”
Section: Type Of the Extraction Solutionmentioning
confidence: 99%
“…Experimentally, they show that less than 10% of the total Mn is in the precipitated form, when the total Mn concentration is less than or equal to 100 mmol L −1 , suggesting a slow kinetics of precipitation. In a recent study, Yalamanchili et al (2022) 81 suggested that under the same conditions the formation of the MnHPO 4 (s) precipitate may not reach equilibrium aer 40 min and could continue to precipitate beyond this time. In our study, this implies that the precipitation of MnHPO 4 (s) can continue in the extracted solution aer ltration.…”
Section: Type Of the Extraction Solutionmentioning
confidence: 99%
“…Among acellular assays, the dithiothreitol (DTT) assay is one of the most commonly used to evaluate the OP of PM (Cui et al, 2023;Yalamanchili et al, 2022;Jiang et al, 2019). It measures the loss of DTT over time when exposed to a PM sample.…”
Section: Introductionmentioning
confidence: 99%